(untitled) (LACCEI, 2024)
The objective was to describe and verify the elements, methodology and main findings of the the elements, methodology and main findings of the research on the study of research related to the study of trends in innovation and sustainability in innovation and sustainability trends in global companies. Out of 124 were reduced to 80 articles after selection based on the PRISMA methodology. PRISMA methodology. The results reflect that the two variables The results reflect that the two variables have a great scope in companies because they their structure, determining relevant factors for their development and their impact on the development and their impact on the outside world.